Instrumentação ultrassônica para caracterização do processo de formação de hidrato - Bostelmann, Pauline (2016)
Currently, among the biggest challenges in oil industry are the hydrates. Hydrates, also known as clathrates, are crystalline structures formed by water connected by hydrogen bonds that are stabilized by a guest molecule. Hydrates are present in nature and they can be formed in some industrial processes, creating obstacles and imposing challenges in the flow assurance area. In oil pipelines, hydrates represent risk and cause difficulties, which may even prevent the flow, causing downtime and losses. There is no technique for monitoring the hydrate formation in industry. Among the instrumentation techniques being proposed one of the most promising is the ultrasound. It has desirable characteristics to the oil industry such as robustness, low cost deployment, easy maintenance, real time operation and non intrusiveness. The main purpose of this dissertation is to identify hydrate formation process, from its early stages, in order to avoid pipe blockages and unnecessary stops of the production. This study was conducted using two test benches, one for static formation and one that provides agitation approaching to real condition of hydrates formation. The benches were cooled with a thermostatic bath, in which hydrate was formed and analyzed using ultrasound by different methods. THF (tetrahydrofuran) was chosen as guest molecule, because it forms hydrates under mild conditions of temperature and pressure, and provides similar structure to hydrates formed by natural gas, present in oil pipelines. Ultrasound signal acquisitions were made during the hydrate formation. The experimental results show changes in the ultrasonic waves and in the acoustic properties, thus enabling to detect the presence and formation of the structure. Using acoustic velocity it was possible to determine hydrates properties such as hydrate growth.